2021
DOI: 10.1108/jtf-09-2021-227
|View full text |Cite
|
Sign up to set email alerts
|

Global tourism in crisis: conceptual frameworks for research and practice

Abstract: Purpose The aims of this Editorial are twofold: (i) synthesise emergent themes from the special issue (ii) tender four theoretical frameworks toward examination of crises in tourism. Design/methodology/approach The thematic analysis of papers highlights a diversity of COVID-19 related crises contexts and research approaches. The need for robust theoretical interventions is highlighted through the four proposed conceptual frameworks. Findings Crises provides a valuable seam from which to draw new empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…Pandemi beberapa waktu lalu memberikan pukulan telak bagi sektor pariwisata (Aldao et al, 2021;Cheer et al, 2021). Pengelolaan serta kunjungan wisata terpengaruh akibat situasi tersebut.…”
Section: Pendahuluanunclassified
“…Pandemi beberapa waktu lalu memberikan pukulan telak bagi sektor pariwisata (Aldao et al, 2021;Cheer et al, 2021). Pengelolaan serta kunjungan wisata terpengaruh akibat situasi tersebut.…”
Section: Pendahuluanunclassified
“…Many publications have been produced the past three years about the impacts of COVID-19 on the tourism and hospitality sector and whether this is a game changer or not (Cheer et al ., 2021; Lew et al ., 2020; Papp et al ., 2023; Tomassini et al ., 2021; Yeoman, 2023). Given that the COVID pandemic is quite a recent phenomenon affecting tourism, most of these papers remain conceptual show scenarios, visions and potential outlooks.…”
Section: Introductionmentioning
confidence: 99%
“…Many publications have been produced the past three years about the impacts of COVID-19 on the tourism and hospitality sector and whether this is a game changer or not (Cheer et al, 2021;Lew (Information about the authors can be found at the end of this article.) Papp et al, 2023;Tomassini et al, 2021;Yeoman, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…When facing the Covid-19 pandemic wave in 2020-2021 (Cheer et al, 2021), teachers and learning activities in almost all provinces in Indonesia implemented a distance learning policy (Wibowo et al, 2022). Distance learning was chosen to reduce the risk of virus transmission due to direct interaction (Munastiwi, 2021).…”
Section: Introductionmentioning
confidence: 99%